20 UMP staff conquered Mount Kinabalu - Mohd Shahrul, Azuar (2019)
September 6, 2019 was a historical and memorable date for 20 Universiti Malaysia Pahang (UMP) staff who successfully scaled the Mount Kinabalu, the highest peak in South East Asia, standing at 4,905.2 metres (13,455 feet) from sea level. According to d’Puncak Expedition Programme Director, Mohd Shahrul Azuar, the participants who were from various faculties underwent physical and mental training by having hiking trainings to ensure that they were fit for the climb.